Sistem Kerja Storage Dan Purchasing Departement Terhadap Kelangsungan Operasional Di Hotel Jambuluwuk Malioboro Yogyakarta - Indri Kholifatun; R. Jati Nurcahyo (Universitas Bina Sarana Informatika, 2018)
Abstract - Hotel Jambuluwuk Malioboro Yogyakarta certainly needs operational equipment, equipment, operational both material and ready to use. The existence of Purchasing Department authorized to make purchases of all hotel goods will facilitate the operational process. With the purchase of goods, the hotel provides a warehouse as a place to store all hotel items held by Storage Department. Storage Department especially receiver in charge of receiving goods orders from Purchasing, while store keeper who organize and serve the demand of goods from other Departments at Hotel Jambuluwuk Malioboro.This research uses descriptive qualitative method that describes the events / events experienced by reality. Working system Storage and Purchasing Department ranging from procurement of goods from the branch, the demand for goods for the user, the purchase of goods, until the acceptance of goods from suppliers. Interconnection during the operation between the Store and Purchasing Department will minimize the obstacles that will occur, so that the professionalism of work will be established for the achievement of satisfaction for guests. Keywords: Storage Department, Purchasing Department, Operational